Kontribusi Advokat dalam Urgensi Pelaksanaan Mediasi dalam Perkara Pidana - Aritonang, Topan Billers; Anggusti, Martono; Panjaitan, Yosua Tahyudi (Mahesa Research Center, 2024)
The active role of advocates in peace efforts is stated in the Indonesian Advocate Code of Ethics (KEAI). This is the role that the author wants to emphasize in the contribution of advocates in the urgency of implementing mediation in criminal cases. With the active involvement of advocates, the peace process which previously only took place in the mediation room can now expand outside the mediation room, through interactions carried out by each legal representative. This article uses normative and qualitative juridical research methods on previous data about lawyers, as well as the results of observations and insights obtained by the author while carrying out internship activities at a law office. The results of this research found that the role of advocates is also important as a catalyst for peace between victims and perpetrators of criminal acts. Advocates act as mediators whose aim is to reach an agreement on compensation for the victim as well as an apology from the perpetrator to the victim as well as a form of accountability from the perpetrator to the victim. If there is peace through agreed mediation, the legal process can be stopped if the reporter (victim) has withdrawn his report to the police (article 75 of the Criminal Code). Ordinary offenses cannot stop the court process. However, in practice, if this occurs during the court process, the agreement between the perpetrator and the victim or the defendant and the victim witness will be a consideration for the judge in mitigating when handing down a decision.